2018
DOI: 10.1371/journal.pone.0197811
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing post-exertional malaise in myalgic encephalomyelitis/ chronic fatigue syndrome: A patient-centered, cross-sectional survey

Abstract: BackgroundPost-exertional malaise (PEM) is considered to be the hallmark characteristic of myalgic encephalomyelitis/ chronic fatigue syndrome (ME/CFS). Yet, patients have rarely been asked in formal studies to describe their experience of PEM.ObjectivesTo describe symptoms associated with and the time course of PEMMethodsOne hundred and fifty subjects, diagnosed via the 1994 Fukuda CFS criteria, completed a survey concerning 11 symptoms they could experience after exposure to two different types of triggers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 44 publications
7
72
1
1
Order By: Relevance
“…Several studies have indicated that the duration of symptoms is possibly a unique aspect of PEM among patients with ME and CFS. For example, Jason et al [12] found that 75% of participants experienced PEM exacerbation more than 24 h after engaging in light activity, a finding comparable to that found by others [13]. …”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Several studies have indicated that the duration of symptoms is possibly a unique aspect of PEM among patients with ME and CFS. For example, Jason et al [12] found that 75% of participants experienced PEM exacerbation more than 24 h after engaging in light activity, a finding comparable to that found by others [13]. …”
Section: Introductionsupporting
confidence: 56%
“…PEM duration had an area under the curve (AUC) of 0.88 ( SE = 0.1, CI = 0.85–0.90, p < 0.001). A previous study [13] indicated that most patients with ME and CFS experience PEM lasting longer than 12 h, whereas some case definitions require lasting more than 24 h [11]. Therefore, the authors examined PEM duration from 14 to 23 h and 24 h or more.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, it could be concluded that both acute physical exercise bout and effects of physical exercise programme can lead to cognitive function improvement in many patient populations. However, in the case of ME/CFS patient's further research on this topic is needed because participation in a physical exercise programme has the potential to induce post-exertional malaise at least in some participants [40]. The high drop-out rate amongst ME/CFS patients in this study with a number of individuals not showing improved cognitive function highlights the need for care in advocating SEP therapy and the potential heterogeneity of this patient group.…”
Section: Discussionmentioning
confidence: 84%
“…peak oxygen uptake, heart rate, rating of perceived exertion (RPE) and blood lactate) is reported for the purpose of characterizing the test and describing the sub-study participants. Borg's RPE scale (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) [29] was administered according to published instructions [30]. is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Laboratory Visitmentioning
confidence: 99%
“…PEM in ME/CFS has also been described as a constellation of extensively disabling signs and symptoms in response to exertion [14]. Historically, there has been difficulty in defining and measuring PEM (see [15,16] for more information), but for the purposes of this study, PEM will be used to denote concepts related to post-exertional symptom exacerbation [15].…”
Section: Introductionmentioning
confidence: 99%